Innovations and technologies in the work of the physical therapist in pelvic strengthening (Research, Society and Development, 2022)
Introduction: Pelvic physiotherapy is an important topic for the improvement of services in the field of physiotherapy, as its treatment is the use of manual techniques and technologies to solve sexual problems that affect women throughout their lives. The work of the physiotherapy professional in the perineal strengthening and recovery of the pelvic floor starts to aim at improving the strength of contraction of the perineal muscles and the prevention of dysfunctions and libidinal incontinence. Objective: To know the innovations and technologies used for the use of physical therapists in pelvic strengthening. Methodology: Bibliographic study with a descriptive qualitative approach, with 33 articles being searched in the databases, namely: Scribd, PubMed, Scielo, carried out between the years 2000 and 2022. Results: It is necessary to know the respective structures and tools used for the treatment types of dysfunctions and their main symptoms. Through strengthening training, it is possible to develop an increase in the diameter and strength of the fibers of the pelvic floor muscles. Conclusion: The use of instruments is of paramount importance to reintegrate women into their sex life and society, aiming at greater speed and efficiency in strengthening the pelvic muscles.